TQM Extension Practices and Performance: A Case Study in Malaysian Aerospace Industry - Soedarso, Sri Widodo (2009)
This research examines the implementation of total quality management (TQM) extension practices and business performance using a case study on Malaysian aerospace industries. The study examines the organization effectiveness and efficiencies, and the level of company performance that complies with the international quality standard, role and regulation of the aerospace authority. Malaysian aerospace industries are expected to expand and significantly contribute to capture value-added high technology, national economic growth, and increasing challenge in a globalization competition marketplace which is expected to become fierce in the year 2015 and beyond. The main objective of this research is to investigate and measure ten variables of TQM, which are leadership, policy and strategy, people and result, partnership and resources, processes quality management, information and analysis, society result, human resources focused,customer satisfaction and requirement. This research also examines the company performance using the criteria of performance excellence such as MBNQA, EFQM, AS/EN9100, AQS D1-9000, National Institute Standard and Technology (NIST),International Aerospace Group of Quality (IAQG), International Aerospace Quality Standard (IAQS), Business Excellent Models (BEM) and others. The result of the reliability test i.e. the Cronbach’s Alpha was extremely reliable. Similarly, the model was accepted and significantly fit. It was found that the variables were significantly associated with the underlying latent variable which measured a total of 81% .The variance was explained by extraction factor sums squared loadings of the information yielded in business performance of Malaysian aerospace firms. The main findings showed that all the two (2) variables i.e. leadership and partnership resources are less influence the business performance of Malaysian aerospace industry. Therefore, it is suggested that firms need to formulate corrective action plans and continuous quality improvements to achieve excellence. Therefore, the following recommendations are identified: (1) improvement of internal and external partnerships, design, product, processes, quality,services, on time delivery; and (2) improvement of employee education, training and development; and focus on qualifying and certifying both personnel and facilities to the customer requirement needed and role regulatory of the international authority aerospace requirement. Consequently, these enable the Malaysian aerospace firms to secure long term contracts, gain trust from partners, have timely payments, ensure the suppliers and customers’ satisfaction, increase the performance level, get new investments from foreign customers, and do business globally. The novelty of this study are the understanding the excellent level of capability of business performance; realized the actual quality practices which have significant effect towards business performance; including the necessary improvements to be carried-out by the companies involved.